2011
DOI: 10.1038/ncb2224
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial regulation of Dia and Myosin-II by RhoGEF2 controls initiation of E-cadherin endocytosis during epithelial morphogenesis

Abstract: E-cadherin plays a pivotal role in epithelial morphogenesis. It controls the intercellular adhesion required for tissue cohesion and anchors the actomyosin-driven tension needed to change cell shape. In the early Drosophila embryo, Myosin-II (Myo-II) controls the planar polarized remodelling of cell junctions and tissue extension. The E-cadherin distribution is also planar polarized and complementary to the Myosin-II distribution. Here we show that E-cadherin polarity is controlled by the polarized regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
284
5
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(322 citation statements)
references
References 68 publications
25
284
5
8
Order By: Relevance
“…Finally, the decrease in E-cadherin staining could be due to its localized endocytosis within the ingressing membrane. In support of this latter hypothesis, endocytosis of E-cadherin has been shown to occur in mitotic cells (Bauer et al, 1998) and, in Drosophila, found to be initiated through activation of RhoGEF2, the formin protein Diaphanous and ROCK (Levayer et al, 2011), all of which are localized in the contractile ring.…”
Section: Generating a New Adhesive Interfacementioning
confidence: 64%
“…Finally, the decrease in E-cadherin staining could be due to its localized endocytosis within the ingressing membrane. In support of this latter hypothesis, endocytosis of E-cadherin has been shown to occur in mitotic cells (Bauer et al, 1998) and, in Drosophila, found to be initiated through activation of RhoGEF2, the formin protein Diaphanous and ROCK (Levayer et al, 2011), all of which are localized in the contractile ring.…”
Section: Generating a New Adhesive Interfacementioning
confidence: 64%
“…During intercalation of the Drosophila germband, for example, actin, nonmuscle myosin II and its regulators accumulate at shrinking junctions, whereas cadherin is enriched at junctions that persist during intercalation (Blankenship et al, 2006;Levayer et al, 2011;Simões et al, 2010;Zallen and Wieschaus, 2004). Asymmetric localization of proteins in epithelial cells that use basolateral protrusive activity during rearrangement has not previously been examined.…”
Section: Discussionmentioning
confidence: 99%
“…7 RhoA signaling is a master regulator of actomyosin cytoskeleton and thus has been implicated in a variety of morphogenetic processes. [31][32][33][34][35][36] While the role for active RhoA signaling in facilitating essential cellular processes has been wellestablished 9,[37][38][39][40][41] there are circumstances where RhoA signaling must be downregulated, either physiologically or pathologically to elicit a biological response. 41,42 Given the importance of the actomyosin cytoskeleton in positively regulating RhoA signaling, 7,[43][44][45] targeting actin-regulators such as Coronin 1B might be one of the approaches to achieve a precise spatiotemporal regulation of RhoA.…”
Section: Resultsmentioning
confidence: 99%